2022
DOI: 10.3390/molecules27227764
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin Decreases Kidney Iron Deposits and Increases Hepcidin Levels in Diabetic Rats with Iron Overload: A Preliminary Study

Abstract: Iron overload (IOL) increases the risk of diabetes mellitus (DM). Capsaicin (CAP), an agonist of transient receptor potential vanilloid-1 (TRPV1), reduces the effects of IOL. We evaluated the effects of chronic CAP administration on hepcidin expression, kidney iron deposits, and urinary biomarkers in a male Wistar rat model with IOL and DM (DM-IOL). IOL was induced with oral administration of iron for 12 weeks and DM was induced with streptozotocin. Four groups were studied: Healthy, DM, DM-IOL, and DM-IOL + C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…On the contrary, the consumption of chili pepper, whose main important component is capsaicin, may not be indicated in patients with anemia with increased hepcidin. In this context, one recent study reported that the chronic administration of capsaicin for 12 weeks increased hepcidin levels in the serum of diabetic mice [101].…”
Section: Nutritional Modulation Of Hepcidinmentioning
confidence: 99%
“…On the contrary, the consumption of chili pepper, whose main important component is capsaicin, may not be indicated in patients with anemia with increased hepcidin. In this context, one recent study reported that the chronic administration of capsaicin for 12 weeks increased hepcidin levels in the serum of diabetic mice [101].…”
Section: Nutritional Modulation Of Hepcidinmentioning
confidence: 99%
“…Iron overload, which is common in diabetes, may trigger or worsen DKD [65]. In an interesting experiment, chronic capsaicin administration was tested in male Wistar rats with iron overload (IOL) and diabetes mellitus + IOL [66]. Capsaicin markedly reduced kidney iron deposits by increasing the circulating levels of hepcidin, an important regulator of iron homeostasis, but had apparently no relevant effects on biomarkers of renal damage such as albuminuria, cystatin C, and beta-2-microglobulin.…”
Section: Diabetic Kidney Diseasementioning
confidence: 99%
“…Another particular note is its influence on the pivotal PI3K-Akt pathway. Studies have unveiled that CAP can modulate the PI3K-Akt pathway at multiple tiers [ 21 , 24 ]. It can stimulate PI3K activity, initiating the phosphorylation and activation of Akt, which subsequently orchestrates downstream events associated with cell proliferation and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations have unveiled its antioxidative, anti-inflammatory, and anticancer attributes [16][17][18][19][20]. Notably, CAP has been found to influence cellular iron metabolism, potentially impacting iron-dependent processes [21]. Specifically, CAP has ability of inhibition ferroptosis in normal tissue to protect it, it regulates ferroptosis through combination with iron, but it also could induce cancer ferroptosis through regulation SLC7A11-GPX4 signaling pathway [22,23].…”
Section: Introductionmentioning
confidence: 99%